OctoEyes - Hayward, Eva (Frontiers in Communication, 2019)
Examining Jean Painlevé's and Geneviève Hamon's film The Love Life of the Octopus (Les Amours de la pieuvre) (1965), this essay offers a theory of refracted spectatorship. Refraction, here, describes the sexual nature of the eye/camera, and also how this refractory sight mis/sees animals, particularly octopuses.